Evidence on Intergenerational Income Transmission Using Complete Dutch Population Data - Fiona Carmichael; Christian Darko; Marco G Ercolani; Ceren Ozgen; W. Stanley Siebert (Institute of Labor Economics (IZA), 2019)
We estimate the intergenerational elasticity (IGE) of income for the Netherlands using complete population data for around 177,000 28-year olds. We find that IGEs are much lower when actual individual income data are used rather than proxies or aggregates for income. Though low, daughters' IGEs are higher than sons' indicating lower income mobility for women.
Keywords: J62; J61; D31; 330; intergenerational elasticity; intergenerational mobility; income; equality of opportunity; Great Gatsby curve; Netherlands